2020
DOI: 10.3892/or.2020.7571
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/AKT/mTOR signaling mediates anticancer effects of epigallocatechin‑3‑gallate in ovarian cancer

Abstract: Epigallocatechin-3-gallate (EGCG), a polyphenol present in green tea, exhibits anticancer effects in various types of cancer. A number of studies have focused on the effects of EGCG on lung cancer, but not ovarian cancer. Previous reports have implicated that EGCG suppressed ovarian cancer cell proliferation and induced apoptosis, but its potential anticancer mechanisms and signaling pathways remain unclear. Thus, it is necessary to determine the anti-ovarian cancer effects of EGCG and explore the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
5
15
0
Order By: Relevance
“…One effect was that microvessel formation was decreased, thereby reducing blood flow to the xenograft. Similar effects were observed in a mouse model of ovarian cancer [ 318 ], suggesting that careful use of such extracts could be useful for the prevention of numerous neoplasms.…”
Section: Plant Derivatives and Hormonessupporting
confidence: 57%
“…One effect was that microvessel formation was decreased, thereby reducing blood flow to the xenograft. Similar effects were observed in a mouse model of ovarian cancer [ 318 ], suggesting that careful use of such extracts could be useful for the prevention of numerous neoplasms.…”
Section: Plant Derivatives and Hormonessupporting
confidence: 57%
“…In the present study, VO downregulated PTEN expression and indirectly activated the PI3K/Akt/mTOR signaling pathway, and then reversed the anticancer effects of NFKBIZ overexpression, which is consistent with previous studies ( 51 - 53 ). Additionally, another study has revealed that high concentration of VO can inhibit hepatocarcinoma cell proliferation and induce senescence ( 54 ).…”
Section: Discussionsupporting
confidence: 93%
“…A study utilising a xenograft model revealed that the administration of a prodrug form of EGCG inhibited the proliferation of tumour cells and enhanced apoptosis in a time and dose-dependent manner, with the significant effect of reducing the formation of microvessels and therefore hindering blood flow to the xenografts [ 229 ]. Similar results were observed in a mouse model of ovary cancer [ 230 ], which suggests that such extracts may prove viable in the prevention of a variety of cancers. The protective potential of green tea exceeds that of black tea; it was suggested that drinking an additional two cups of green tea daily can reduce the risk of EC by 25% [ 231 ].…”
Section: Tea As An Element Of Prophylaxis and Pharmacotherapy Supplem...supporting
confidence: 79%